Equivalent viscous damping ratio for a RC column under seismic load after a fire. Issue 1 (January 2021) - Tamrazyan, Ashot; Chernik, Vladimir
Abstract: The problem of taking into account combinations of special influences in the design of buildings and structures is currently quite relevant. In the event of a combination of fire and seismic load, two options are possible: fire after an earthquake and an earthquake after a fire. This work is devoted to the development of the methodology for calculating RC columns when the second option appears. It is known that fire effects reduce the mechanical characteristics of concrete and reinforcement. When calculating for seismic loads, it is also important to understand how the properties of a structure change during heating to dissipate deformation energy under low-cycle loads. When calculating RC columns using the displacement based design (DBD) method, dissipative properties are estimated the viscous damping ratio. In this work, this ratio is determined by considering the energy losses in one cycle of oscillations, which are equal to the area of the hysteresis loop. Hysteresis loops are determined by numerical calculation of RC columns for a combination of vertical preload and quasistatic horizontal displacement. The mechanical properties of the columns correspond to different fire times: 0, 30, 60, 90 and 120 minutes. In numerical modeling, it was found that the total energy that the column is capable of dissipating decreases with increasing duration of fire exposure. In its turn the hysteresis damping ratio at different fire duration can be either more or less than its initial value. The hysteresis damping coefficient decreases only for a time of fire of 30 and 60 min. With a longer fire duration (90 and 120 min), the coefficient does not decrease.